Method for reducing content of metal ions in perfluorinated sulfonic acid resin

Through electrolysis and cation exchange column purification methods, metal ions in perfluorosulfonic acid resin can be efficiently removed, solving the problems of high cost and complicated procedures in existing technologies, achieving efficient and environmentally friendly metal ion removal effects, and significantly extending the service life of fuel cell membranes.

CN120757681APending Publication Date: 2025-10-10FUJIAN HAIDEFU NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510762752.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The existing methods for reducing the metal ion content in perfluorosulfonic acid resins are costly and complex, making large-scale production difficult.

Method used

By dissolving perfluorosulfonic acid resin in a solvent, filtering, diluting and electrolyzing it, the electric field is used to drive the metal ions to migrate to the cathode for deposition or enter the electrolyte solution, combined with sodium cation exchange column purification to achieve efficient removal of metal ions.

Benefits of technology

It achieves efficient removal of metal ions in perfluorosulfonic acid resin, with a removal rate of over 90%, significantly restoring the proton exchange capacity of the sulfonic acid group, extending the service life of the fuel cell membrane, simplifying waste liquid treatment, and meeting the requirements of green chemical industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757681A_ABST
    Figure CN120757681A_ABST
Patent Text Reader

Abstract

Aiming at the problems of high cost and tedious procedures of a method for reducing the content of metal impurities in perfluorinated sulfonic acid resin in the prior art, the invention provides a method for reducing the content of metal ions in perfluorinated sulfonic acid resin, which comprises the following steps: dissolving perfluorinated sulfonic acid resin in a solvent to obtain a mixed solution; filtering the mixed solution to obtain a perfluorinated sulfonic acid resin dispersion liquid, and diluting the perfluorinated sulfonic acid resin dispersion liquid; and electrolyzing the diluted perfluorinated sulfonic acid resin dispersion liquid, and then performing post-treatment to obtain a purified perfluorinated sulfonic acid resin solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorine chemical industry, and particularly relates to a method for reducing the metal ion content in perfluorosulfonic acid resin and application thereof. Background Art

[0002] Perfluorosulfonic acid resins are widely used in proton exchange membrane fuel cells, hydrogen production from water electrolysis, energy storage batteries, and as catalysts in organic synthesis. The prepared perfluorosulfonic acid resins are melt-extruded or solution-cast to form perfluorosulfonic acid membranes. Before membrane formation, the metal ion content of the perfluorosulfonic acid resins must be tested. This metal ion content directly affects the chemical properties and, consequently, the membrane's service life. Therefore, preparing a perfluorosulfonic acid resin with a low metal ion content is crucial.

[0003] Several methods have been proposed in the prior art for reducing the metal ion content in fluoropolymers. For example, these methods use high-purity raw materials to produce the fluoropolymers. However, these methods are extremely costly, and even using only high-purity raw materials, they cannot avoid the introduction of metal ions during the production process, resulting in limited success. Another approach is to use cation exchange resins to remove iron ions from aqueous fluoropolymer dispersions. However, the process is complex and unsuitable for large-scale production.

[0004] Therefore, there is a need in the art for a method that can quickly and efficiently reduce the content of metal impurities in perfluorosulfonic acid resin to prepare high-purity perfluorosulfonic acid resin. Summary of the Invention

[0005] Aiming at the problems of high cost and complicated procedures in the prior art methods for reducing the metal impurity content in perfluorosulfonic acid resin, the present invention provides a method for reducing the metal ion content in perfluorosulfonic acid resin.

[0006] The technical solutions adopted by the present invention to solve the above technical problems are as follows: The present invention provides a method for reducing the metal ion content in a perfluorosulfonic acid resin, comprising the following steps: dissolving perfluorosulfonic acid resin in a solvent to obtain a mixed solution; filtering the mixed solution to obtain a perfluorosulfonic acid resin dispersion, and diluting the perfluorosulfonic acid resin dispersion; The diluted perfluorosulfonic acid resin dispersion is electrolyzed and then post-treated to obtain a purified perfluorosulfonic acid resin solution.

[0007] Optionally, electrolyzing the diluted perfluorosulfonic acid resin dispersion comprises the following steps: The diluted perfluorosulfonic acid resin dispersion was introduced into the electrolytic cell at a constant voltage of 1.5-3 V and a current density of 0.5-15 mA / cm 2, electrolyze at 25~60℃ for 4~24h.

[0008] Optionally, when the valence of the metal ions in the perfluorosulfonic acid resin dispersion is greater than 1, electrolysis is performed at a constant voltage of 2 to 2.5 V for 4 to 12 hours; When the valence of the metal ions in the perfluorosulfonic acid resin dispersion is 1, the current density is 8-15 mA / cm 2 Next electrolysis.

[0009] Optionally, the cathode of the electrolytic cell is graphite, the anode is titanium coated with ruthenium, and the diaphragm is a perfluorosulfonic acid resin diaphragm.

[0010] Optionally, before filtering the mixed solution, the following steps are further included: heating a portion of the mixed solution to 80-150° C. at 0.5-1.2 MPa and reacting for 4-6 hours to obtain a reaction solution; After the reaction liquid is cooled, the remaining mixed solution is added to the reaction liquid in batches, with each addition amount being 1% to 3% of the mass of the reaction liquid, and then the temperature is raised to 120 to 140° C. for reaction until the solid content in the reaction liquid is 15% to 20%.

[0011] Optionally, diluting the perfluorosulfonic acid resin dispersion comprises the following steps: adding water to the perfluorosulfonic acid resin dispersion to dilute the perfluorosulfonic acid resin dispersion; The diluted perfluorosulfonic acid resin dispersion is then ultrasonicated for 1 to 4 hours.

[0012] Optionally, the solid content of the diluted perfluorosulfonic acid resin dispersion is 0.2% to 1%.

[0013] Optionally, the solvent is water and an organic solvent, and the mixed solution includes 1% to 8% perfluorosulfonic acid resin, 20% to 75% water and 17% to 75% organic solvent.

[0014] Optionally, the organic solvent includes one or more of ethanol, n-propanol, isopropanol, N,N-dimethylformamide, and N-methylpyrrolidone.

[0015] Optionally, the post-treatment includes purifying the electrolyzed perfluorosulfonic acid resin dispersion through a sodium-type cation exchange column.

[0016] In the present invention, the hydrophilic sulfonic acid groups (-SO3 -) is fully exposed, and then the metal ions in the perfluorosulfonic acid resin dispersion are directionally migrated by electrolysis, thereby efficiently removing the metal ions adsorbed in the perfluorosulfonic acid resin. In particular, this method can achieve a metal ion removal rate of more than 90%, avoiding the breakage of sulfonic acid groups or degradation of the polymer main chain caused by high temperature or strong acid environment, and can significantly restore the proton exchange capacity of the sulfonic acid group, so that the liquid phase conductivity of the membrane is increased to a level close to that of the untreated hydrogen-type perfluorosulfonic acid resin, significantly extending the service life of the fuel cell diaphragm, and effectively solving the problems of long cycle and high residue of the traditional acid washing method. At the same time, this method does not require the addition of additional oxidants or chelating agents. It only drives the metal ions to migrate directionally to the cathode for deposition or enter the electrolyte solution through the electric field. The waste liquid treatment is simple and there is no secondary pollution, which meets the requirements of green chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an electron microscope image of the untreated perfluorosulfonic acid resin in Comparative Example 2; Figure 2 is an electron microscope image of the perfluorosulfonic acid resin after treatment in Example 1; Figure 3 This is an electron microscope image of the untreated perfluorosulfonic acid resin in Comparative Example 1; Figure 4 This is an electron microscope image of the perfluorosulfonic acid resin after treatment in Comparative Example 1. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] The present invention provides a method and application for reducing the metal ion content in perfluorosulfonic acid resin, comprising the following steps: dissolving perfluorosulfonic acid resin in a solvent to obtain a mixed solution; filtering the mixed solution to obtain a perfluorosulfonic acid resin dispersion, and diluting the perfluorosulfonic acid resin dispersion; The diluted perfluorosulfonic acid resin dispersion is electrolyzed and then post-treated to obtain a purified perfluorosulfonic acid resin solution.

[0020] In this embodiment, the hydrophilic sulfonic acid groups (-SO3 - ) is fully exposed, and then the metal ions (such as Na + , Ca 2+ 、Fe 3 +), thereby efficiently removing the metal ions adsorbed in the perfluorosulfonic acid resin. In particular, the removal rate of the metal ions can reach more than 88% by the method, avoiding the sulfonic acid group rupture or the polymer main chain degradation caused by high temperature or strong acid environment, and significantly restoring the proton exchange ability of the sulfonic acid group, so that the liquid phase conductivity of the perfluorosulfonic acid resin membrane is increased to a level close to that of the hydrogen type perfluorosulfonic acid resin before treatment, significantly prolonging the service life of the fuel cell separator membrane, and effectively solving the problems of long cycle and high residue of the traditional acid washing method. At the same time, the method does not need to add additional oxidizing agent or complexing agent, and only through the electric field driving the metal ions to migrate to the cathode or into the electrolyte solution, the waste liquid treatment is simple and there is no secondary pollution, which meets the requirements of green chemical industry.

[0021] It can be understood that the method for reducing the content of metal ions in the perfluorosulfonic acid resin can also be applied to precious metal recovery, which has economic and universality.

[0022] In some embodiments, the diluted perfluorosulfonic acid resin dispersion is electrolyzed, including the following steps: The diluted perfluorosulfonic acid resin dispersion is passed into an electrolytic cell, and electrolyzed at a constant voltage of 1.5-3V, a current density of 0.5-15mA / cm 2 , 25-60℃ for 4-24h. By electrolyzing at this temperature, the dispersion state of the perfluorosulfonic acid resin molecular chain can be accurately controlled, and the sulfonic acid group rupture or the polymer main chain degradation caused by high temperature or strong acid environment can be avoided.

[0023] Specifically, as shown in Figure 1 and Figure 2 , it is verified by transmission electron microscopy (TEM) that the treated perfluorosulfonic acid resin dispersion still maintains a uniform nanoscale dispersion structure, the film mechanical strength (tensile strength ≥20 MPa) and the chemical stability, i.e. Fenton test ≥200h, are equivalent to those of the untreated resin, and the service life of the fuel cell separator membrane is significantly prolonged.

[0024] In some embodiments, when the valence of the metal ions in the perfluorosulfonic acid resin dispersion is greater than 1, the electrolysis is carried out at a constant voltage of 2-2.5V for 4-12h. When the valence of the metal ions is greater than 1, the metal ions have high affinity, and by using this voltage for electrolysis, the perfluorosulfonic acid resin can be prevented from being overoxidized.

[0025] When the valence of the metal ions in the perfluorosulfonic acid resin dispersion is 1, the electrolysis is carried out at a current density of 8-15mA / cm 2 . When the valence of the metal ions is 1, the migration rate of the metal ions is low during the electrolysis process, and by using this current density, the removal of the monovalent metal ions can be accelerated.

[0026] In some embodiments, the electrolytic cell comprises a graphite cathode, a titanium-coated ruthenium anode, and a perfluorosulfonic acid resin diaphragm. The graphite cathode facilitates metal ion reduction, while the titanium-coated ruthenium anode prevents the generation of chlorine during electrolysis.

[0027] Specifically, the electrolytic cell can be a single-chamber electrolytic cell or a dual-chamber electrolytic cell, or multiple stages of electrolysis can be connected in series to achieve continuous production. Experimental verification shows that the process parameters based on 100g of perfluorosulfonic acid resin can be directly scaled up to a ton-level scale, shortening the production cycle to less than 10 hours. Compared with the traditional acid regeneration method (i.e., the treatment method of Comparative Example 1), its purification efficiency is significantly improved.

[0028] In some embodiments, before filtering the mixed solution, the method further comprises the following steps: heating a portion of the mixed solution to 80-150° C. at 0.5-1.2 MPa and reacting for 4-6 hours to obtain a reaction solution; After the reaction liquid is cooled, the remaining mixed solution is added to the reaction liquid in batches, with each addition amount being 1% to 3% of the mass of the reaction liquid, and then the temperature is raised to 120 to 140° C. for reaction until the solid content in the reaction liquid is 15% to 20%.

[0029] By partially dissolving the mixed solution under pressure first, and then adding the remaining mixed solution in batches until the solid content in the reaction solution is 15%~20%, it is avoided that the perfluorosulfonic acid resin dissolves at high temperature, which causes the sulfonic acid groups in the perfluorosulfonic acid resin to break or the polymer main chain to degrade.

[0030] Specifically, when a portion of the mixed solution is heated, the perfluorosulfonic acid resin is stirred and immersed in the remaining mixed solution, so that the perfluorosulfonic acid resin is fully swollen.

[0031] Furthermore, the mixed solution is reacted under nitrogen or argon to avoid the risk of solvent volatilization and oxidative decomposition of the perfluorosulfonic acid resin. The stirring speed of the mixed solution during the reaction is 500-800 r / min.

[0032] In some embodiments, diluting the perfluorosulfonic acid resin dispersion comprises the following steps: adding water to the perfluorosulfonic acid resin dispersion to dilute the perfluorosulfonic acid resin dispersion; The diluted perfluorosulfonic acid resin dispersion is then ultrasonically treated for 1-4 hours to fully dissolve the metal ions in the perfluorosulfonic acid resin dispersion. By diluting the perfluorosulfonic acid resin dispersion with water, the electrolysis process uses water as the medium, eliminating the need for additional oxidants or complexing agents. The metal ions are driven solely by the electric field to migrate toward the cathode for deposition or enter the electrolyte solution. This simplifies wastewater treatment and eliminates secondary pollution, meeting green chemical industry requirements.

[0033] In some embodiments, the solid content of the diluted dispersion of the perfluorosulfonic acid resin is 0.2% to 1%. The purified perfluorosulfonic acid resin solution can be adapted to the solid content requirement (0.5%-2%) of the existing fuel cell membrane coating process without additional adjustment of the film forming parameters.

[0034] In some embodiments, the solvent is water and an organic solvent, and the mixed solution comprises 1% to 8% perfluorosulfonic acid resin, 20% to 75% water, and 17% to 75% organic solvent. By using mixed solvents to synergistically swell, the hydrophilic sulfonic acid groups (-SO3 - ) of the perfluorosulfonic acid resin are fully exposed.

[0035] Specifically, the perfluorosulfonic acid resin can be divided into two parts to prepare the mixed solution, one part is dissolved at high pressure, and the other part is soaked for sufficient swelling, and is ready for subsequent replenishment. Preferably, the content of perfluorosulfonic acid resin in the standby mixed solution is 5% to 8%.

[0036] In some embodiments, the organic solvent comprises one or more of ethanol, n-propanol, isopropanol, N,N-dimethylformamide, and N-methylpyrrolidone.

[0037] Preferably, the organic solvent is selected from one or more of ethanol, n-propanol, and isopropanol, and the content of the organic solvent in the mixed solution is 20% to 60%. By using alcohol solvents and water to dissolve the perfluorosulfonic acid resin, the use of highly toxic solvents is avoided, and the environment is friendly.

[0038] Further, in a preferred embodiment, the mass ratio of ethanol, n-propanol, and water in the solvent is 3:3:2.

[0039] In some embodiments, the post-treatment comprises purifying the electrolyzed dispersion of the perfluorosulfonic acid resin through a sodium-type cation exchange column, and the sodium-type cation exchange column traps the precipitates or metals that fall off from the electrode in the perfluorosulfonic acid resin dispersion.

[0040] The application is further illustrated by the following examples.

[0041] Example 1 300 g of hydrogen-type perfluorosulfonic acid resin (containing Fe³⁺ 500 ppm, Ca²⁺ 300 ppm) was taken.

[0042] 100 g of hydrogen-type perfluorosulfonic acid resin (5%), 712 g of ethanol, 712 g of n-propanol, and 476 g of pure water (mass ratio of ethanol, n-propanol, and water is 3:3:2) were added to a four-fluorine-lined reaction kettle to obtain a mixed solution. The air was replaced with nitrogen, and the stirring speed was 500 r / min. The temperature was raised to 150°C, and the reaction was carried out at 1.2 MPa for 4 hours to obtain a reaction liquid.

[0043] The remaining 200 g of hydrogen-type perfluorosulfonic acid resin was dissolved in 1424 g of ethanol, 1424 g of n-propanol, and 952 g of pure water for pre-swelling and set aside.

[0044] After cooling the reaction mixture in the reactor, the standby hydrogen-type perfluorosulfonic acid resin mixed solution was added in portions, each adding 3% of the reaction mixture's mass. The reaction was continued at 120°C for 2 hours, until the final solids content in the reaction mixture reached 15%, indicating a hydrogen-type perfluorosulfonic acid content of 15%. The reaction mixture was filtered, and the filtrate was diluted to 1% solids to obtain a perfluorosulfonic acid resin dispersion, which was then sonicated for 2 hours. The sonicated perfluorosulfonic acid resin dispersion was passed through a dual-chamber electrolytic cell (with a perfluorosulfonic acid membrane separating the anode and cathode) and electrolyzed at 25°C for 4 hours under a constant voltage of 2 V and a current density of 1 mA / cm². The electrolyzed perfluorosulfonic acid resin dispersion was then purified by passing it through a sodium cation exchange column to obtain a perfluorosulfonic acid resin solution.

[0045] Compared to the untreated hydrogen-form perfluorosulfonic acid resin, the purified perfluorosulfonic acid resin achieved a 95% Fe⁺ removal rate and a 93% Ca⁺ removal rate. Liquid-phase conductivity recovered to 98% of that of the untreated hydrogen-form perfluorosulfonic acid resin. The membrane exhibited a tensile strength of 22 MPa and withstood the Fenton test for 220 hours, with no sulfonic acid group breakage.

[0046] Example 2 The method is basically the same as Example 1, except that 300 g of hydrogen-type perfluorosulfonic acid resin (containing 800 ppm of Na⁺) is used, and the dissolution process and the ratio of solvent added are the same as those in Example 1. The solid content in the final reaction solution is 15%.

[0047] The filtrate was diluted to 1% solid content to obtain a perfluorosulfonic acid resin dispersion, which was then ultrasonically treated for 3 hours. The sonicated perfluorosulfonic acid resin dispersion was passed into a dual-chamber electrolytic cell (with a perfluorosulfonic acid membrane separating the anode and cathode) and electrolyzed at 60°C for 4 hours under a constant voltage of 2.5 V and a current density of 15 mA / cm². The electrolyzed perfluorosulfonic acid resin dispersion was then purified by passing it through a sodium cation exchange column.

[0048] Compared to the hydrogenated perfluorosulfonic acid resin before treatment, the purified perfluorosulfonic acid resin achieved a 92% Na⁺ removal rate and restored conductivity to 96%. The membrane also exhibited stable mechanical properties (tensile strength of 21 MPa) and withstood the Fenton test for 210 hours.

[0049] Example 3 The method is basically the same as Example 1, except that the content of hydrogen-type perfluorosulfonic acid resin in the mixed solution is 8%.

[0050] Example 4 The method is basically the same as Example 1, except that the content of hydrogen-type perfluorosulfonic acid resin in the mixed solution is 1%.

[0051] Example 5 The method is basically the same as Example 1, except that the mass ratio of ethanol, n-propanol and water in the mixed solution is 2:2:15, and the content of the organic solvent is 20%.

[0052] Example 6 The method is basically the same as Example 1, except that the mass ratio of ethanol, n-propanol and water in the mixed solution is 1:1:17, and the content of the organic solvent is 10%.

[0053] Example 7 The method is basically the same as Example 1, except that the mass ratio of ethanol, n-propanol and water in the mixed solution is 8:8:3, and the content of the organic solvent is 80%.

[0054] Comparative Example 1 Take 100g of hydrogen-type perfluorosulfonic acid resin (containing Fe³⁺ 500 ppm, Ca²⁺ 300 ppm, Na⁺ 800 ppm).

[0055] Acid Washing: Soak the hydrogenated perfluorosulfonic acid resin in a 20% sulfuric acid solution (solid-to-liquid ratio of 1:10) at 80°C for 12 hours with stirring at 200 rpm. Filter the resin and wash it with deionized water until the solution is neutral (pH = 7). Repeat the acid wash step three times.

[0056] Post-treatment: The hydrogenated perfluorosulfonic acid resin was redispersed in an ethanol / water mixture (volume ratio 1:1), ultrasonically treated for 2 hours, and tested for performance after drying.

[0057] Compared to the untreated hydrogen-form perfluorosulfonic acid resin, the purified perfluorosulfonic acid resin achieved metal ion removal rates of 85% for Fe³⁺, 78% for Ca²⁺, and 65% for Na⁺ (residual Fe³⁺ 75 ppm, Ca²⁺ 66 ppm, and Na⁺ 280 ppm). The sulfonic acid groups were partially cleaved after treatment (infrared spectroscopy showed a 15% decrease in the -SO³⁻ peak intensity), resulting in a proton conductivity of only 82% of the untreated resin. The membrane tensile strength dropped to 16 MPa, and the Fenton test resistance time was shortened to 120 hours.

[0058] Comparative Example 2 Take 100g of hydrogen perfluorosulfonic acid resin (containing Fe³⁺ 500 ppm, Ca²⁺ 300 ppm) as the blank control group without purification treatment.

[0059] The hydrogen-type perfluorosulfonic acid resins treated in the above examples and comparative examples were subjected to metal ion content testing, Fenton resistance test, infrared strength testing, mechanical strength testing, and liquid phase conductivity testing.

[0060] The metal ion content test method is as follows: for the examples, 1-2 mL of the dispersion was taken into a PTFE digestion bottle, 5 mL of concentrated nitric acid (65%) and 1 mL of hydrogen peroxide (30%) were added, and the temperature was gradually increased to 180°C (20 min) and maintained for 30 min. After cooling, the mixture was transferred to a volumetric flask, and the volume was adjusted to 50 mL with ultrapure water. The mixture was filtered (0.22 μm) and passed into an ICP-MS for determination of the metal ion content.

[0061] For the comparative example, 100 g of the purified perfluorosulfonic acid resin was placed in 100 mL of ion extraction solution (20% by mass of ultra-high purity nitric acid), soaked at 60° C. for 24 hours, and then cooled to measure the metal ion content using ICP-MS.

[0062] Fenton resistance test: The materials of the examples and comparative examples were dissolved and then coated. The films were cut into 2 cm × 2 cm sheets, immersed in ultrapure water for 24 hours, and then vacuum-dried (60°C, 12 hours) and weighed (initial weight W0).

[0063] Immerse the vacuum-dried membrane in Fenton's reagent at 80°C for 72-200 hours in the dark.

[0064] After the experiment was terminated, the membrane was removed and vacuum dried again and weighed W1.

[0065] Infrared intensity detection: For the examples, the purified perfluorosulfonic acid resin solution was drop-coated on a clean KBr salt plate, and the solvent was evaporated under an infrared lamp to form a thin film, which was then tested using a Fourier transform infrared spectrometer; For the comparative example, 1 mg of the purified hydrogen-type perfluorosulfonic acid resin particles was ground with 200 mg of dry KBr powder, and then pressed into tablets, which were then tested using a Fourier transform infrared spectrometer.

[0066] Mechanical Strength Testing: Dissolve the materials from both the Examples and Comparative Examples and apply them to films. Cut the films into 2 x 16 cm rectangles and store them at 23 ± 1°C and 50 ± 5% relative humidity for at least 40 hours. Set the initial strain rate to 0.5, the clamp spacing to 100 mm, and the clamp separation rate to 50 mm / min. Prepare five samples per test set, and average the results.

[0067] The test results are entered in Table 1.

[0068] Table 1 The test data from Examples 1-7, Comparative Examples 1, and 2 in Table 1 demonstrate that the method for reducing the metal ion content in perfluorosulfonic acid resin of this embodiment achieves a metal ion removal rate exceeding 88%. Furthermore, the liquid-phase electrical conductivity of the perfluorosulfonic acid resin membrane is increased to a level approaching that of the untreated hydrogen-form perfluorosulfonic acid resin. The membrane's mechanical strength and chemical stability are comparable to those of the untreated resin.

[0069] As can be seen from the test data of Examples 1, 3, and 4 in Table 1, when the content of hydrogen-type perfluorosulfonic acid resin in the hydrogen-type perfluorosulfonic acid resin mixed solution to be purified increases, the contact surface area of ​​the hydrogen-type perfluorosulfonic acid resin particles in the solution increases, some of the hydrogen-type perfluorosulfonic acid resin particles undergo cross-linking to form a gel, and the gel breaks up during stirring, causing the solution viscosity to increase significantly, resulting in an increase in the resistance to metal ion migration during the electrolysis process and a decrease in the metal ion removal rate. When the content of hydrogen-type perfluorosulfonic acid resin in the hydrogen-type perfluorosulfonic acid resin mixed solution to be purified decreases, the hydrogen-type perfluorosulfonic acid resin in the mixed solution has less contact area, no gel is formed, and there is no effect on the viscosity of the mixed solution. The difference in metal ion removal rate is relatively small, indicating that a low-viscosity system is more conducive to sufficient ion migration.

[0070] The test data from Examples 1 and 5-7 in Table 1 show that when the organic solvent content in the hydrogen-type perfluorosulfonic acid resin mixed solution to be purified is less than 17%, the proportion of organic solvent in the mixed solution decreases, resulting in incomplete dissolution of the resin (the ratio of residual undissolved resin particles to the total amount of resin to be treated is ≥5%). The molecules in the undissolved resin cannot relax, and the sulfonic acid groups on the surface of the resin particles are not fully exposed. However, in the dissolved resin, the sulfonic acid groups on the surface of the resin particles are fully exposed. Therefore, when electrolysis is performed after filtration, the purification effect of the dissolved resin is not affected, and the metal ion removal rate remains stable. When the organic solvent content in the hydrogen-type perfluorosulfonic acid resin mixed solution to be purified is greater than 75%, although the resin is completely dissolved, the organic solvent content in the diluted dispersion before electrolysis is high. The organic solvent does not participate in the electrolysis process, resulting in a decrease in electrolyte conductivity, hindering the directional migration of metal ions to the cathode, and significantly reducing the metal ion removal rate during the electrolysis process.

[0071] Further, by Figures 1 to 4 It can be seen that the perfluorosulfonic acid resin dispersion treated by the method of reducing the metal ion content in the perfluorosulfonic acid resin of this embodiment still maintains a uniform nano-scale dispersion structure, indicating that the microscopic dispersion of the resin is not destroyed during the electrolysis process. Figure 4In the middle, the larger particle size can be observed to have agglomerated, and the distribution is not uniform, which indicates that multiple acid washing affects the micro-dispersion structure of the dispersion liquid. In the comparative example, the tensile strength and Fenton resistance test both decrease, which shows that the structure of the perfluorosulfonic acid resin changes after acid washing, which causes the strength of the perfluorosulfonic acid resin to decrease, and the service life is affected.

[0072] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, and improvement within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for reducing the metal ion content in perfluorosulfonic acid resin, characterized in that: The following steps are involved: dissolving perfluorosulfonic acid resin in a solvent to obtain a mixed solution; filtering the mixed solution to obtain a perfluorosulfonic acid resin dispersion, and diluting the perfluorosulfonic acid resin dispersion; The diluted perfluorosulfonic acid resin dispersion is electrolyzed and then post-treated to obtain a purified perfluorosulfonic acid resin solution.

2. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 1, characterized in that: The diluted perfluorosulfonic acid resin dispersion is electrolyzed, comprising the following steps: The diluted perfluorosulfonic acid resin dispersion was introduced into the electrolytic cell at a constant voltage of 1.5-3 V and a current density of 0.5-15 mA / cm 2 , electrolyze at 25~60℃ for 4~24h.

3. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 2, characterized in that: When the valence of the metal ions in the perfluorosulfonic acid resin dispersion is greater than 1, electrolysis is performed at a constant voltage of 2 to 2.5 V for 4 to 12 hours; When the valence of the metal ions in the perfluorosulfonic acid resin dispersion is 1, the current density is 8-15 mA / cm 2 Next electrolysis.

4. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 2, characterized in that: The cathode of the electrolytic cell is graphite, the anode is titanium coated with ruthenium, and the diaphragm is a perfluorosulfonic acid resin diaphragm.

5. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 1, characterized in that: Before filtering the mixed solution, the method further comprises the following steps: heating a portion of the mixed solution to 80-150° C. at 0.5-1.2 MPa and reacting for 4-6 hours to obtain a reaction solution; After the reaction liquid is cooled, the remaining mixed solution is added to the reaction liquid in batches, with each addition amount being 1% to 3% of the mass of the reaction liquid, and then the temperature is raised to 120 to 140° C. for reaction until the solid content in the reaction liquid is 15% to 20%.

6. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 1, characterized in that: Diluting the perfluorosulfonic acid resin dispersion comprises the following steps: adding water to the perfluorosulfonic acid resin dispersion to dilute the perfluorosulfonic acid resin dispersion; The diluted perfluorosulfonic acid resin dispersion is then ultrasonicated for 1 to 4 hours.

7. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 6, characterized in that: The solid content of the diluted perfluorosulfonic acid resin dispersion is 0.2% to 1%.

8. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 1, characterized in that: The solvent is water and an organic solvent, and the mixed solution includes 1% to 8% of perfluorosulfonic acid resin, 20% to 75% of water and 17% to 75% of the organic solvent.

9. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 8, characterized in that: The organic solvent includes one or more of ethanol, n-propanol, isopropanol, N,N-dimethylformamide, and N-methylpyrrolidone.

10. The method for reducing the metal ion content in perfluorosulfonic acid resin according to claim 1, characterized in that: The post-treatment includes purifying the electrolyzed perfluorosulfonic acid resin dispersion through a sodium-type cation exchange column.